Application of Swirl Type Microbubble Generator Aerator Technology in Koi Fish Farming Business in Kentong Village: Penerapan Teknologi Aerator Microbubble Genertor Tipe Swirl pada Usaha Tambak Ikan Koi Desa Kentong - Drajat Indah Mawarni (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
This community service program implements swirl type microbubble generator (MBG) aerator technology to increase the productivity of koi fish farming in Kentong Village. The activity partner is Aim Koi Farm with a production capacity of 10,000 fish on 2 hectares of land. MBG technology works by producing micro-sized air bubbles (50-100 μm) through a swirl flow mechanism, which increases the surface area of ​​oxygen-water contact, thereby improving dissolved oxygen (DO) levels. Implementation begins with the installation of an aeration system, followed by measuring water quality parameters (DO, temperature, pH) using a water quality checker periodically for 30 days. Monitoring results showed a significant increase in DO levels from 4.2 ± 0.3 mg/L to 6.8 ± 0.4 mg/L (p<0.05). The positive impact was seen in a decrease in fish mortality by 15.2% and an increase in daily growth rate by 1.2 g/day. This program proves the effectiveness of MBG as an appropriate solution to increase the productivity of small-scale koi fish farming.